RESPON PERTUMBUHAN EKSPLAN BIJI LIMAU KUIT DENGAN PENAMBAHAN HORMON IBA DAN BAP SECARA IN VITRO - Heri Kurniawan; Eny Dwi Pujawati; Adistina Fitriani (Universitas Lambung Mangkurat, 2020)
This research purposes to determine seed growth of limau kuit explant by tissue culture with arranger growth IBA and BAP. This research is expected to give advantage for alternative supply limau kuit seeding by tisuue culture and give scientific information for develop best quality limau kuit seedling. Data collection and this research from weekly observations limau kuit explant. The results of the studySshowed that theecombination treatment of concentration withhthe addition of ZPT in the form of IBA and BAP gave a visible response to the concentration of treatment A with the addition of IBA and BAP hormones of 0.5 Ppm and treatment of B with the addition of the hormones IBA and BAP respectively 1 Ppm is more stimulating to the formation of shoots in limau kuit seeds while in treatment C with the addition of the hormones IBA and BAP respectively as much as 2 Ppm and Treatment D with the addition of IBA and BAP hormones as much as 4 Ppm each stimulates root growth. Based on all the experiments from the observed data, there were 15 explants that experienced new organ growth and 2 explants that formed a small callus after being observed for 8 weeks.Keywords: explan; growth regulating agent; Limau kuit